Recruitment of multiple stakeholders to health services research: Lessons from the front lines - Kho, Michelle E (BioMed Central, 2010)
BACKGROUND: Self-administered surveys are an essential methodological tool for health services and knowledge translation research, and engaging end-users of the research is critical. However, few documented accounts of the efforts invested in recruitment of multiple different stakeholders to one health services research study exist. Here, we highlight the challenges of recruiting key stakeholders (policy-makers, clinicians, guideline developers) to a Canadian Institutes of Health Research (CIHR) funded health services research (HSR) study aimed to develop an updated and refined version of a guideline appraisal tool, the AGREE. METHODS: Using evidence-based methods of recruitment, our goal was to recruit 192 individuals: 80 international guideline developers, 80 Canadian clinicians and 32 Canadian policy/decision-makers. We calculated the participation rate and the recruitment efficiency. RESULTS: We mailed 873 invitation letters. Of 838 approached, our participation rate was 29%(240) and recruitment efficiency, 19%(156). One policy-maker manager did not allow policy staff to participate in the study. CONCLUSIONS: Based on the results from this study, we suggest that future studies aiming to engage similar stakeholders in HSR over sample by at least 5 times to achieve their target sample size and allow for participant withdrawals. We need continued efforts to communicate the value of research between researchers and end-users of research (policy-makers, clinicians, and other researchers), integration of participatory research strategies, and promotion of the value of end-user involvement in research. Future research to understand methods of improving recruitment efficiency and engaging key stakeholders in HSR is warranted.